Evaluation of the Ocular Tolerance of Three Tacrolimus Topical Pharmaceutical Preparations by Bovine Corneal Opacity and Permeability Test. (2nd July 2016) - Pastor-Clerigues, Alfonso; Serrano, Adela; Milara, Javier; Marti-Bonmati, Ezequiel; Lopez-Perez, Francisco J.; Garcia-Montanes, Sara; Sanfeliu, Joan; Saval-Victoria, Ana C.; Cortijo, Julio
ABSTRACT: Purpose : Tacrolimus ocular preparations are commonly employed in autoimmune or inflammatory ocular disorders. However, currently there are not yet approved ocular formulations. Tacrolimus ocular side effects have been reported in clinical use, so the evaluation of different pharmaceutical preparations is mandatory. In this study, the local corneal tolerance and safety profile of three common tacrolimus 0.03% pharmaceutical preparations were evaluated. Material and methods : Corneal irritation and permeability of tacrolimus preparations were evaluated with the bovine corneal opacity and permeability (BCOP) test. Complementary corneal hematoxylin/eosin and immunohistochemistry staining for tight junctions and adherent junctions E-cadherin, VE-cadherin and zonula occludens-1 were examined and scored to evaluate and to confirm corneal disruption and irritation scores obtained with the BCOP method. Results : Commercial brand ointment (Protopic®), topical compounded eye ointment (pharmacy elaboration) and tacrolimus suspension eye drops (elaborated from parenteral prograf®) were tested as potential ocular preparations to be used in clinics. Tacrolimus preparations hereby studied do not alter the opacity and permeability of the bovine cornea by more than three units, measured by the In Vitro Irritancy Score, neither affected the immunohistochemical parameters, composite score or transepithelial electrical resistance. Conclusions : Tacrolimus preparations studied can be safely applied as a topical ocular treatment.